The influence of legislation on the occurrence of corruption in the administrative institutions of Bosnia and Herzegovina / Adela Plakalo, M. A., Hazim Okanović, M. A. and Salaahuddin Abdibegović, M. A. - Plakalo, M. A, Adela; Okanović, M. A., Hazim; Abdibegović, M. A., Salaahuddin (2021)
Namely, the term corruption comes from the Latin word "corrumpere", which means to corrupt, corrupt, morally corrupt, bribe, bribe someone with money or other material goods (Klaić, 1962). A detailed definition can be found in international documents, primarily in the Council of Europe's Civil Law Convention on Corruption. Bosnia and Herzegovina is a signatory to the Convention, according to which corruption means demanding, offering, giving, or accepting, directly or indirectly, bribes or any other illegal benefit or the possibility of obtaining such benefit, which interferes with the proper performance of any duty or conduct required of the recipient. bribes, illegal benefits, or opportunities to acquire such benefits (Civil Law Convention on Corruption, 1999). The definition of corruption in domestic legislation we can find, through criminal legislation, where corrupt acts are defined as criminal acts, on the other hand, explicit definitions are established by the Law on the Agency for Prevention of Corruption and Coordination of Anti-Corruption (Official Gazette of BiH): 103/09 and 58/13) and the Law on Protection of Persons Reporting Corruption in the Institutions of Bosnia and Herzegovina ("Official Gazette of BiH" No. 100/13). According to the Law in, the Agency for Prevention of Corruption and Coordination of the contest against Corruption in BiH, the term corruption refers to any abuse of power entrusted to a public official or a person in a political position at the level of government in BiH, which may lead to private gain. In addition to the above definitions of corruption, there are many others, both within legal theory and international documents, such as the United Nations Convention against Corruption (UNCAC), Criminal Law, and Civil Convention on Corruption. As well, the above definitions sufficiently reflect the complexity of the concept of corruption, both in linguistic and substantive terms.